挖掘机工作装置逆运动学分析的杆组方法和运动规划 - 魏永泉; 蓝兆辉 (Jixie chuandong)
The Assur-group method is used for inverse kinematic analyzing of excavator working device.And relationship between the position and speed of the excavator working device components and the bucket tooth,and the length,speed,and flow of each hydro cylinder are obtained.And taking maximum-minmum optimization of instantaneous total flow of working device as target to plan the motion of working device is also presented.